Immunological Response of Bovine Mammary Cell Lines in Mastitis and Milk Hygiene - Abd, Abdul-Hadi Abbass (The Iraqi Journal of Veterinary Medicine, 2012)
Mammary adherent cells (MAC-T) were infected with six isolates of Streptococcus uberis (S. uberis). Three isolates were cases of mastitis in dairy cows and belonged to clonal complex 5, 143, which is associated with virulence and three were from cows with no clinical or laboratory evidence of mastitis. All these isolates belonged to clonal complex 86 which contains strains of low virulence. After incubation at 37oC for 24 h, there were no significant differences in the number of adherent or internalized S. uberis between mastitis (M) and non- mastitis (NM) isolates (p> 0.05).The levels of tumour necrosis factor (TNF-α), measured in treated MAC-T cells supernatant with S. uberis by ELISA, were significantly elevated in cultures infected with NM isolates compared with M isolates, after 10h (p>0.05) and 24h (p>0.001) respectively. Expression of TNF-α, TLR2, TLR4 and NFkB genes were examined by Real-Time PCR. There are highly significant differences in the timing of expression. The levels of TNF-α mRNA increased 36 fold after 6 hour of infecting cells with M strains, but not in NM strains of S. uberis. These results suggest a vital role for TNF-α, in the defence against S. uberis in the bovine mammary glands.